2002
DOI: 10.1088/0953-8984/14/10/302
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of transient gels in colloid-polymer mixtures

Abstract: The addition of non-adsorbing polymer to a suspension of colloidal hard-spheres causes phase separation via the depletion mechanism. At high enough concentration of polymer a variety of non-equilibrium aggregation behaviour is observed. Transient gelation is one such behaviour observed at the highest polymer concentrations. Transient colloid-polymer gels are metastable space-filling particle networks. They persist for some finite time before suddenly collapsing to form a dense sediment. Thus transient gels exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
144
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(155 citation statements)
references
References 22 publications
9
144
2
Order By: Relevance
“…Previous studies [13,24] of gel collapse have suggested that the mechanism of collapse depends sensitively on the initial height h 0 of the gel. Gels formed in short sample cells display steady or 'creeping' sedimentation where the height falls continuously with age at a rate which decays exponentially with time while taller samples show sudden collapse.…”
Section: A Collapse Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [13,24] of gel collapse have suggested that the mechanism of collapse depends sensitively on the initial height h 0 of the gel. Gels formed in short sample cells display steady or 'creeping' sedimentation where the height falls continuously with age at a rate which decays exponentially with time while taller samples show sudden collapse.…”
Section: A Collapse Dynamicsmentioning
confidence: 99%
“…Sudden or 'delayed' network collapse is observed in a wide variety of materials [7][8][9][10][11][12][13][14][15][16] and seems to be ubiquitous at small U c /k B T . However, while sudden collapse * Corresponding author:P.Bartlett@bristol.ac.uk has been attributed to channel formation within the gel [12,13], the microscopic processes operating have never been fully established. A better microscopic understanding of the origin of sudden gel collapse is important not only because the distinctive settling behavior is intriguing from a scientific viewpoint but also because a quantitative prediction of gel stability is a critically important issue in the formulation and manufacture of many commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…Although they exhibit solid-like mechanical properties, colloidal gels are easily disrupted by small perturbations, such as gravitational forces. While a large body of macroscopic observations of gels under gravitational stress exists [5][6][7][8][9][10][11][12][13], very little is known on the microscopic processes at play during sedimentation, thus limiting our ability to understand and predict the behavior of sedimenting gels.Here, we use a novel light scattering method to gain access to the dynamics of a slowly settling colloidal system from the macroscopic deformation of the sample down to the relaxational behavior at the particle scale. We find that the very slow macroscopic deformation occurs via irreversible plastic events at the microscopic scale.…”
mentioning
confidence: 99%
“…37 At high enough particle and/or polymer concentrations, the dynamics is arrested for some time in a gel state before slow restructuring leads to loss of mechanical stability and a rapid collapse to form an amorphous sediment. 25,31,38 For this reason, these structures are also known as transient gels.…”
mentioning
confidence: 99%